Miscarriage but not fecundity is associated with progression of joint destruction in rheumatoid arthritis. Issue 8 (12th July 2004) - van Dunné, F M; Lard, L R; Rook, D; Helmerhorst, F M; Huizinga, T W J
Abstract : Objective: To determine whether reproductive history before disease onset is associated with severity of joint destruction in rheumatoid arthritis. Methods: A special early arthritis clinic (EAC) was established at the department of rheumatology of Leiden University Medical Centre. General practitioners were encouraged to refer patients with joint complaints to this clinic, where the diagnosis of rheumatoid arthritis was made by a rheumatologist. In all, 113 female patients with definite rheumatoid arthritis were included in this study. A structured questionnaire was administered and joint damage was assessed by sequential x rays of the hands and feet, using the modified Sharp score. Results: The length of time of unprotected intercourse until first pregnancy (fecundity) was comparable with data from earlier studies, with 16% of the patients reporting a time to first pregnancy of more than 12 months. Fecundity did not reflect the extent of joint damage over time. The miscarriage rate was 15% per pregnancy, comparable to population figures (12–15%). A significant increase in joint damage over a two year follow up was found in patients with rheumatoid arthritis who had experienced at least one miscarriage compared with those who had never had a miscarriage (mean modified Sharp scores at 2 years, 24 (95% confidence interval, 15 to 32) and 16 (10 to 23), respectively; p<0.05). At baseline, the Sharp scores were similar in the two subgroups. Conclusions: Miscarriage before disease onset but not fecundity is associated with the progression of joint damage in rheumatoid arthritis.